Assessing and Addressing the Need for Cancer Patient Education in a Resource‐Limited Setting in Haiti. (8th June 2020) - Schleimer, Lauren E.; Desameau, Peter‐Gens; Damuse, Ruth; Olsen, Maia; Manzo, Veronica; Cardenas, Carlos; Mehrtash, Hedieh; Krakauer, Eric L.; Masamba, Leo; Wang, Catharine; Bhatt, Ami S.; Shulman, Lawrence N.; et al.
Abstract: Purpose: Misinformation and lack of information about cancer and its treatment pose significant challenges to delivering cancer care in resource‐limited settings and may undermine patient engagement in care. We aimed to investigate patients' knowledge and attitudes toward cancer and its treatment and to adapt, implement, and evaluate a low‐literacy cancer patient education booklet at the Hôpital Universitaire de Mirebalais (HUM) in rural Haiti. Materials and Methods: A low‐literacy cancer patient education booklet was adapted into Haitian Creole in collaboration with clinicians at HUM. Patients were recruited for structured interviews ( n = 20) and two focus groups ( n = 13) designed to explore patients' attitudes toward cancer and its treatment and to assess whether the booklet increased patients' knowledge via an investigator‐designed knowledge test. Results: Participants reported a subjective lack of knowledge about cancer and its treatments and described views of cancer as deadly or incurable. Patients of varying education levels valued receiving written materials that set expectations about cancer treatment and expressed a desire to share the booklet with caregivers and others in their community. Participants across all levels of education significantly increased their performance on a knowledge test after counseling using the booklet ( p < .001). Conclusion: We found that an educational booklet about cancer developed in collaboration with local providers was well received by patients with variable literacy levels and improved their knowledge of cancer and its treatment in a resource‐limited setting. Such educational materials have the potential to serve as tools to engage patients with cancer and their families in care. Implications for Practice: Misinformation and lack of information pose significant challenges to delivering cancer care in resource‐limited settings; however, there are often no culturally and literacy appropriate tools available to aid in patient education. This article shows that written educational materials are well received by patients of variable literacy levels and can be effective tools for increasing patients' knowledge of cancer and its treatment in a limited‐resource setting. Furthermore, the authors have made their educational booklet, Cancer and You, freely available online and welcome the opportunity to connect with readers of The Oncologist interested in implementing this educational booklet in clinical care. Abstract : New efforts are being made to bring modern cancer medicine to patients in low‐ and middle‐income countries. This article describes an educational tool that could enhance patient–provider communication and promote adherence to treatment by helping patients understand cancer and its treatment.